Karakterisasi Bakteri Amilo-Termofilik Obligat dari Sumber Air Panas Semurup, Sungai Penuh - - Jumawita; Anthoni Agustien; Djong Hon Tjong (Jurnal Biologi Universitas Andalas, 2014)
The study about “characterization of amilo-thermophilic obligat bacteria from Semurup Hot Spring” has been conducted from November 2013 to March 2014 in Laboratory of Microbiology, Biology Department, Faculty of Mathematic and Natural Science, Andalas University, Padang. The purpose of this study was to find out and analyze isolate amilo-thermophilic obligat bacteria. The result of this study showed that isolate SII-7 from Semurup Hot Spring survived at 70 ºC, that produced amylase with unique macroscopic characters: random, cream and smooth surface. The isolate SII-7 was bacille, Gram positive, has endospore as a product, motility and catalase positive.Keyword: Characterization, thermophilic obligat, bacteria, amylase.